Structural performance of light steel framing panels using screw connections subjected to lateral loading. (December 2017) - Henriques, J.; Rosa, N.; Gervasio, H.; Santos, P.; da Silva, L. Simões
Abstract: Screw connections have an important role in the performance of Light Steel Framing (LSF) construction systems. In this paper, the behaviour LSF panels using screw connections subjected to lateral load is discussed and further insights are provided on the behaviour of such panels by experimental tests and numerical analysis. Therefore, the main aims of this paper are: (i) to provide a discussion on the analytical, experimental and numerical assessment of steel-to-steel connections, between cold-formed elements, and steel-to- Oriented-Strand-Board (OSB) connections; (ii) to discuss the results of the experimental tests carried out on braced and unbraced LSF panels subjected to lateral load; and (iii) based on a calibrated numerical model, to provide further insights into the behaviour of LSF panels. The paper may be subdivided into two main parts. The first part of the paper addresses the behaviour of the screw connections; while the second part addresses the behaviour of braced and unbraced LSF panels, subjected to lateral loading. The major conclusions of this paper are: (i) the results presented in this paper confirm a relevant contribution of the OSB board to the lateral stiffness of the LSF panel; (ii) the connections between OSB boards and the steel frame are the governing part of the panel resistance to lateral loading; and (iii) the significant contribution of the OSB board shows that it should not be neglected, as it is currently the case in the European standard EN 1993-1-3. Highlights: Experimental tests and numerical simulations on shear screw connections between cold-formed profiles. Analytical evaluation and discussion of the tests on shear screw connections between cold-formed profiles. Experimental tests on shear screw connections between thin steel sheet and OSB. Analytical evaluation and discussion on the tests on shear screw connections between thin steel sheet and OSB. Analytical model, experimental tests and numerical simulations on LSF panels with and without OSB subjected to lateral loading.